Recombinant Analogue of Varicella Zoster Virus Glycoprotein E: Cloning, Expression and Studying of AntigEn Properties - G. I. Alatortseva; A. V. Sidorov; L. N. Nesterenko; L. N. Luhverchik; I. I. Amiantova; V. V. Docenko; Phong Pham Huy; A. V. Milovanova; O. B. Vylivannaya; A. C. Kazanova; V. V. Lavrov; V. V. Zverev (Эпидемиология и вакцинопрофилактика)
We made recombinant antigen GE containing fragment of VZV glycoprotein E (Gly48 - Glu135) fused to E. coli beta-galactosidase and confirmed its antigen specificity by Western blotting and competitive-inhibition enzyme immunoassay (EIA) in comparison with commercial analogues and natural viral antigens. We showed interaction of recombinant GE protein with IgG antibodies from rabbits immunized by vaccine viral strain. GE protein also specifically reacted in ELISA with 66% of sera from zoster patients and 35% of sera from control groups including sera containing antibodies to other herpes viruses, sera from healthy donors, and sera from patients with different forms of intestinal disorders. Consequently, we demonstrated possibility of application of our recombinant GE VZV as antigen for diagnostics and research use.